Fool's Errand - Hobb, Robin (London Harper Voyager, 2001)
Return to the world of the Farseers... Robin Hobb's best loved characters, Fitz , The Fool and Nighteyes the wolf, face new adventures and trials in the first book of The Tawny Man trilogy.
Keywords: Fantasy fiction -- Princes -- Fantasy fiction, American